Morphologic and Immunohistochemical Characteristics of Fluorescent In Situ Hybridization Confirmed TFE3-Gene Fusion Associated Renal Cell Carcinoma: A Single Institutional Cohort. (November 2020) - Akgul, Mahmut; Saeed, Omer; Levy, David; Mann, Steven A.; Cheng, Liang; Grignon, David J.; Eble, John N.; Idrees, Muhammad T.
Abstract : TFE3 -fusion associated renal cell carcinoma ( TFE3 -RCC) accounts for up to 5% adults and 40% of childhood RCC. Their comprehensive immunohistochemical (IHC) profile in correlation to fluorescence in situ hybridization (FISH) testing and their role in the diagnostic approach are not well documented because of lacking published data. FISH confirmed TFE3- RCC between years 2010 and 2020 were identified from institutional electronic database and retrospectively reviewed. Eighty-five TFE3 -RCC were identified. Seventy-six of 85 (89.4%) TFE3- RCC cases had positive TFE3 expression, with diffuse and strong/moderate TFE3 expression in 45 (54.2%). Three (3.5%) TFE3 -RCC had negative TFE3 expression whereas 6 (7%) cases had equivocal TFE3 expression. On the other hand, positive TFE3 -IHC expression was observed in 17/29 (58.6%) TFE3 -FISH negative RCC cases, although only 8 (27.5%) had diffuse and moderate/strong TFE3 expression. Diffuse and strong TFE3 -IHC expression was statistically significant in predicting TFE3 -FISH positivity ( P <0.0001) regardless of morphologic features. After univariate and multivariate analyses, TFE3 -IHC was the only parameter with significant predictive value for detecting positive TFE3 -FISH ( P <0.0001). On univariate analysis, sex, classic morphology, age, negative AE1/AE3 or cytokeratin 7 were not predictive of TFE3 -FISH positivity. Diffuse and strong nuclear TFE3 -IHC expression is significantly associated with TFE3 -FISH positivity and can be used as a surrogate marker to confirm translocation associated cases. TFE3 -rearranged RCCs show variable histomorphologic features and TFE3 -FISH should be performed in cases presenting at a younger age or, regardless of the age, tumors with unusual morphology. Despite previous reports, negative pancytokeratin and positive cathepsin K expression may not be reliable markers for TFE3 -RCC.